Leisure activities, out of school learning and employment for the student of the 3rd high school in the spectrum of the daily free time (extracurricular) - Λιάμπας Τάσος; Τουρτούρας Χρήστος (The Greek Review of Social Research, 2012)
The study examines the pupil’s activities of the 3rd degree of high school after the end of the school day. It correlates main factors, such socio-economic and educational level of the pupil’s family, his/her gender, graduation and access to higher education, which compose his profile with activities that are, repetition of school «working life» (e.g., tutorial school) and, more rarely, real work and also, with those who give meaning in leisure (e.g. companionships, music etc.).